FEATURES OF DIRECT AND ADVANCED DEVELOPMENT OF SCIENCE OF THE DEPARTMENT OF LIFE SAFETY AND ENGINEERING ECOLOGY AT KHARKIV STATE UNIVERSITY OF CIVIL ENGINEERING AND ARCHITECTURE - Юрченко, Валентина; Даньшева, Світлана; Шилін, Віктор (New Collegium, 2020)
The global environmental crisis in the mid-twentieth century caused the rapid development of applied fields of ecology, including the doctrine of the environmental security. its nature protection part was mainly provided by technical solutions. This facilitated the opening of the departments of ecology in technical schools and the greening of their specific areas of engineering. The Department of Life Safety and Engineering Ecology at Kharkiv State University of Civil Engineering and Architecture scientifically masters and develops not only the monitoring of technogenically loaded ecosystems, but also the search for technical solutions that reduce this load. The main directions of its work are: ecological safety of biosphere environments and life safety in them; environmental problems of the construction industry, urban development and urban economy, greening of urban development. The most successful and implemented scientific works include the identification of environmental hazards of atmospheric air pollution by the emission of fine particulate organic particles (which are pathogens, allergens and a mediated source of greenhouse gases), the development of technology to protect from them. it has been experimentally proved that ionization reduces the concentration of fine particulate organic particles in atmospheric air to the normatively acceptable level. The most interesting works of another direction include the solution of environmental problems of the sewer systems operation and the video ecology of small architectural forms of this technical field. installations of degassers for purification of gaseous emissions from sewage networks at locations among residential buildings, parks and recreational zones, in areas of the city with historical development created acute visual dis- comfort — video pollution. Design proposals for design solutions to improve the video ecological characteristics of degassing installations and harmonize them with the environment have been developed.